The Role of Diagnostic Assessments in Learning Pancasila Education - Azmi, Nur; Adi, Panggih Nur; Saragih, Siti Zahara; Hubi, Zindan Baynal (CV. Rayyan Dwi Bharata, 2025)
This study aims to determine the effect of diagnostic assessment in Pancasila Education learning. This research method uses a literature review conducted by reading, analyzing and synthesizing journals, books, or literature that is in accordance with the topic. The results of this study are that the effect of diagnostic assessment related to learning styles in the perspective of Pancasila Education learning that the learning styles that occur in students are visual, auditory, and kinesthetic. Teachers are expected to facilitate learning according to learning styles through improvisation of learning methods. The effect of cognitive diagnostic assessment in Pancasila Education learning plays a role in determining initial knowledge. The form of cognitive diagnostic assessment can be in the form of descriptive or multiple choice questions conventionally and the use of technology with the help of quiziz learning applications, google forms, etc. While the benefits of diagnostic assessment are as a map of Pancasila Education learning, differentiation learning, Teaching At The Rights Level, and creating the concept of school well-being.